LO37: Prevalence of cigarette smoking amongst adult emergency department patients. (May 2019) - Tolmie, A.; Erker, R.; Oyedokun, T.; Sullivan, E.; Graham, T.; Stempien, J.
Abstract : Introduction : Tobacco smoking is a priority public health concern, and a leading cause of death and disability globally. While the smoking prevalence in Canada is approximately 13-18%, the proportion of smokers among emergency department (ED) patients has been found to be significantly higher. This disparity primes the emergency department as a critical environment to provide smoking cessation counselling and support.Methods : A verbal questionnaire was administered to adult patients (18+) presenting to Royal University, Saskatoon City, and St. Paul's Hospital ED's. Patients were excluded if they were underage, too ill, or physically/mentally unable to complete the questionnaire independently. Patients' smoking habits were also correlated with Fagerstrom tobacco dependence scores, chief complaints, Canadian Triage Acuity Scale (CTAS) scores, and willingness to partake in ED specific cessation counselling. Data were analyzed using IBM SPSS software to determine smoking prevalence and compared to Statistics Canada data using chi-square tests.Results : In total, 1190 eligible patients were approached, and 1078 completed the questionnaire. Adult Saskatoon ED patients demonstrated a cigarette smoking prevalence of 19.6%, which is significantly higher than the general adult Saskatchewan public at 15.1% (p < 0.0001). Comparing smoking and non-smoking cohorts, there are no significant differences in CTAS scores (p = 0.60). Of the proposed cessation interventions, ED cessation counselling was most popular among patients (62.4%), followed by receiving a pamphlet (56.2%), and being contacted by a smokers' quit line (49.5%). Out of the smoking cohort, 51.4% indicated they want to quit smoking, and would be willing to partake in ED-specific cessation counselling, if available. Additionally, 88.1% of current smokers started smoking when they were less than 19 years old.Conclusion : The higher smoking prevalence demonstrated in ED patients highlights the need for a targeted intervention program that is feasible for the fast-paced environment. Quit attempts have been demonstrated to be more efficacious with repeated interventions, which could be achieved by training ED staff to conduct brief motivational interviews and faxing referrals to a smokers' quit line for follow-up. Furthermore, pediatric ED's could be a valuable location for cigarette smoking screening, as the majority began smoking in their adolescence.